Las aproximantes espańolas, entre la teoría y la práctica - Szałek, Jerzy (Wydawnictwo Naukowe UAM, 2008)
One of the phonetic curiosities of the modern Spanish language is the occurrence of a group of voiced allophones [ ß, R, y] in its phonetic and phonological system, at present defined by Spanish specialists in phonetics as "aproximantes" which are the realisation of /b, d, g/ phonemes inside words and between words. The paper presents the acoustic and articulatory basis for their detachment from the group of the fricative allophones and a detailed way of articulation. The issue of their articulatory stabilisation within the system of standard and non-standard Spanish is also raised. Additionally, the author of the paper pays special attention to problems of articulation in the process of teaching the above-named allophones in phonetics classes designed for the students of the Spanish philology.
Spanish "aproximantes" - between theory and practice
Keywords: Spanish "aproximantes"; Spanish language; Phonetics